2022
DOI: 10.1002/capr.12532
|View full text |Cite
|
Sign up to set email alerts
|

Self‐perceived clinical competence, gender and workplace setting predict burnout among psychotherapists

Abstract: Burnout is a public health challenge, particularly in human service professions. The syndrome was defined in the 1970s as a reaction to long-lasting work-related stress, especially experienced by people working in human service professions. It comprises three different reactions: emotional exhaustion, depersonalisation and reduction in personal accomplishment (Maslach et al., 2001). Burnout is a problem for individuals and an economic burden for society due to healthcare costs, sick leave and high turnover (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Some signs of what has been conceptualised as burnout and secondary stress can also be found in the therapists' narratives (Ekundayo et al., 2013; Quintana, 2005; Santana & Farkas, 2007). Working in the public sector may be a factor influencing this negative impact (Spännargård et al., 2023). This is clearly described by the therapists who participated in this study, who are critical of the organisation and suggest certain improvements that should be implemented by institutions in charge of treating children and adolescents who have been victims of sexual violence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some signs of what has been conceptualised as burnout and secondary stress can also be found in the therapists' narratives (Ekundayo et al., 2013; Quintana, 2005; Santana & Farkas, 2007). Working in the public sector may be a factor influencing this negative impact (Spännargård et al., 2023). This is clearly described by the therapists who participated in this study, who are critical of the organisation and suggest certain improvements that should be implemented by institutions in charge of treating children and adolescents who have been victims of sexual violence.…”
Section: Discussionmentioning
confidence: 99%
“…Working in the public sector may be a factor influencing this negative impact (Spännargård et al, 2023). This is clearly described by the therapists who participated in this study, who are critical of the organisation and suggest certain improvements that should be implemented by institutions in charge of treating children and adolescents who have been victims of sexual violence.…”
Section: Con Clus Ionsmentioning
confidence: 95%
“…In a sample of 1121 mental health providers, Sprang et al (2007) found that approximately 13% were at high risk for compassion fatigue or burnout. Likewise, in a sample of 327 psychotherapists, Spännargård et al (2022) found that 62% reported moderate to high levels of burnout due to personal or work-related issues, often influenced by variables that dysregulate the exosystem. Furthermore, for immigrant mental health professionals, they are also balancing a new macrosystem.…”
Section: Burnout For Mental Health Professionalsmentioning
confidence: 99%
“…Previous studies have shown differing levels of burnout between caring professions [ 4 , 5 , 6 , 7 ]. The reasons for these differences are not fully understood and are likely to be due to a complex and multi-faceted combination of each staff group’s unique challenges and characteristics.…”
Section: Background and Introductionmentioning
confidence: 99%